2011
DOI: 10.1530/rep-11-0149
|View full text |Cite
|
Sign up to set email alerts
|

Conceptus-mediated endometrial vascular changes during early pregnancy in mares: an anatomic, histomorphometric, and vascular endothelial growth factor receptor system immunolocalization and gene expression study

Abstract: This work examined how the conceptus modulates endometrial tissue remodeling and vascular development prior to implantation in mares. A macroscopic uterine examination was completed at day 21 of pregnancy. In situ morphology revealed that the endometrium involved in encroachment is restricted to the dorsal endometrium immediately overlying the yolk sac. The amount of stromal area occupied by blood vessels and the number of endometrial glands were increased during early pregnancy. Endometrial histomorphometry a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 44 publications
1
25
0
2
Order By: Relevance
“…In correlation with the observation that the genes assigned to the functional categories blood circulation and angiogenesis were predominantly found in the expression clusters with highest mRNA concentrations during estrus and in expression clusters with highest mRNA concentrations on Days 8 or 12, studies of uterine blood flow in cyclic mares found highest blood flow on Days 0 and 10/11 [55,56]. The comparison to studies of gene expression during the time around MRP [14,16] shows that expression of similar genes is induced during estrus and on Days 12 and 14 of pregnancy, indicating a specific induction of those genes by the presence of the conceptus, probably by conceptus estrogens.…”
Section: Genes Related To Angiogenesis Vasculature Development and mentioning
confidence: 65%
See 1 more Smart Citation
“…In correlation with the observation that the genes assigned to the functional categories blood circulation and angiogenesis were predominantly found in the expression clusters with highest mRNA concentrations during estrus and in expression clusters with highest mRNA concentrations on Days 8 or 12, studies of uterine blood flow in cyclic mares found highest blood flow on Days 0 and 10/11 [55,56]. The comparison to studies of gene expression during the time around MRP [14,16] shows that expression of similar genes is induced during estrus and on Days 12 and 14 of pregnancy, indicating a specific induction of those genes by the presence of the conceptus, probably by conceptus estrogens.…”
Section: Genes Related To Angiogenesis Vasculature Development and mentioning
confidence: 65%
“…In addition to genes involved in PG metabolism and signaling, a number of other genes involved in regulation of cyclic changes in the endometrium have been investigated, such as estrogen and P4 receptor genes [15], genes related to endometrial vascular changes [16], and wingless-type (WNT) genes and their antagonists [17]. To get a holistic overview of dynamic gene expression changes during the estrous cycle in equine endometrium, a DNA microarray analysis of endometrial biopsy samples was performed, which were collected at five defined time points of the estrous cycle: Day 16 (beginning of follicular phase), Day 0 (day of ovulation), Day 3 (early luteal phase), Day 8 (midluteal phase), and Day 12 (late luteal phase).…”
Section: Introductionmentioning
confidence: 99%
“…Steady expression levels of ESR1 are important when studying estrogen‐responsive genes and indeed explants can be used to study the regulation of estrogen‐responsive genes such as Milk fat globule‐EGF factor 8 (unpublished observation). VEGF plays a role in plays an important role in endometrial angiogenesis (Silva et al, ). Increased expression as a sequel to hypoxia has been reported for human endometrial cells in culture; given the three‐dimensional structure of explants, an increase in expression following in vitro culture can be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical detection of the proliferation marker Ki‐67 antigen monitors mitotic activity in the mare endometrium (Silva et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…These proteins are suitable for comparative analysis as they have different functions during reproductive cycle and inflammatory reaction and are well established in the immunohistochemical evaluation of pregnant and cyclic equine endometrium. Immunohistochemical detection of the proliferation marker Ki-67 antigen monitors mitotic activity in the mare endometrium (Silva et al 2011).…”
Section: Introductionmentioning
confidence: 99%